BalletVR: a Virtual Reality System for Ballet Arm Positions Training - Barioni, Ricardo; Costa, Willams; Aleluia, Alessandra; Teichrieb, Veronica (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2019: Anais do XXI Simpósio de Realidade Virtual e Aumentada, 2019)
In a ballet studio, the teacher plays an important role in the process of learning positions and movements. However, there are occasions where the student needs to practice while the teacher is unavailable. In this situation, the student has no orientation and is likely to create bad habits during training, which may lead to worse results than before. In this work, we present the BalletVR, a Virtual Reality Kinect-based application for guiding ballet dancers through the practice of basic ballet arm positions. The results show our system’s potential to be used by students as an alternative for autonomous ballet basic positions training.